(untitled) (Research, Society and Development, 2024)
Ankyloglossia, or alteration of the lingual frenulum, is a congenital anomaly in which a small portion of tissue that should have undergone apoptosis during embryonic development remains present on the sublingual surface. The aim of this study was to report a clinical case of the diagnosis and treatment of ankyloglossia in a newborn who underwent frenotomy. The methodology used was the Clinical Case Report, supported by a review of the literature related to the case to provide the theoretical basis. Case report: A newborn female patient, seen by the multidisciplinary team in the maternity ward, was referred to the pediatric dentist 30 days after birth, for evaluation of the lingual frenulum "tongue test", and was diagnosed with ankyloglossia, submitted to lingual frenotomy and then breastfed. He responded well to post-surgery and gained weight as a result of being able to breastfeed properly. We conclude that the importance of diagnosing and treating these newborns is essential, since ankyloglossia can cause various problems, such as difficulties in breastfeeding, speech disorders, poor oral hygiene and bullying during childhood and adolescence.